Cyclosporin but not tacrolimus significantly increases salivary cytokine contents in rats - Spolidório, Luis Carlos [UNESP]; Holzhausen, Marinella [UNESP]; Palomari Spolidorio, Denise M. [UNESP]; Nassar, Carlos A. [UNESP]; Nassar, Patricia O. [UNESP]; Muscará, Marcelo Nicolás (Wiley, 2005)
Background: Cyclosporin (CsA) and tacrolimus (FK-506) are immunosuppressive drugs that specifically inhibit T-cell activation via calcineurin inhibition. Gingival overgrowth is a common side effect following the administration of CsA. The severity of gingival overgrowth seen in patients taking FK-506 is less than that observed with CsA. Little is known about the involvement of saliva in drug-induced gingival overgrowth. The purpose of this study was to investigate the salivary contents of tumor growth factor β1 (TGF-β1), epidermal growth factor (EGF), and interleukin-6 (IL-6) as well as the hystometry of gingival tissue obtained from rats treated with either FK-506 or CsA. Methods: For 30 or 60 days rats received daily subcutaneous injection doses of either CsA or FK-506 (10 mg/kg). The concentrations of TGF-β1, EGF, and IL-6 in saliva were determined by enzyme-linked immunosorbent assay, and after histological processing, the oral epithelium and connective tissue were assessed at the region of the lower first molars. Results: The levels of TGF-β1, EGF, and IL-6 in saliva were not significantly altered by any of the treatments after 30 days. After 60 days of treatment with CsA, gingival overgrowth and significant increase in salivary TGF-β1, EGF, and IL-6 concentrations were observed; no statistically significant changes were induced by FK-506. Conclusion: Within the limits of this experimental study, it can be concluded that CsA, but not FK-506, induced gingival overgrowth associated with an increase of the salivary levels of the cytokines TGF-β1, EGF, and IL-6.
Keywords: Animal studies; Cyclosporin A/adverse effects; Gingival hyperplasia/etiology; Growth factors, epidermal; Growth factors, tumor β1; Interleukin-6; Saliva/analysis; Tacrolimus/adverse effects; cyclosporin; cytokine; epidermal growth factor; interleukin 6; tacrolimus; transforming growth factor beta1; animal experiment; animal model; animal tissue; concentration response; connective tissue; controlled study; enzyme linked immunosorbent assay; fibroblast; gingiva overgrowth; histometry; male; molar tooth; mouth mucosa; nonhuman; rat; salivation; Animals; Cyclosporine; Cytokines; Epidermal Growth Factor; Gingival Overgrowth; Immunosuppressive Agents; Male; Rats; Rats, Sprague-Dawley; Saliva; Tacrolimus; Transforming Growth Factor beta; Transforming Growth Factor beta1